Identifikasi Serangga Semak di Sekitar Pusat Pendidikan Konservasi Alam Bodogol, Bogor, Jawa Barat - Nur Is Farida; Aulia Mustika Parmadini; Syahkila Cahya Ardiana; Abdul Haris Anugrah Syahbani; Hanum Isfaeni; Rosi Fitri Ramadani (Biocaster : Jurnal Kajian Biologi, 2026)
This study aims to identify shrub insect species around the Bodogol Nature Conservation Education Center (PPKA Bodogol), Bogor, West Java. The research uses an exploratory descriptive approach by sampling through the free roaming method on shrub vegetation. Specimens were collected using sweeping net and hand collecting techniques from morning to noon, then analyzed descriptively based on the number of individuals, the number of species, and the composition of the order and family. The results of the study recorded 20 species from 8 orders, with the dominance of Orthoptera (7 species) and Lepidoptera (4 species). The families Acrididae and Scarabaeidae are the most abundant taxons, while Xylotrupes gideon is the species with the highest number of individuals. The dominance of these families and species indicates that the vegetation of the PPKA Bodogol bush provides habitat conditions that support herbivorous and detritivore insects that play an important role in energy flow and ecosystem stability. These findings show that shrub vegetation has a strategic role as a functional habitat for insects and can be used as basic data in planning, management, and conservation of insect biodiversity in conservation areas.